A Greenpreneurship Framework for Okra Business to Global Sustainability - Mulyono, Resha Dwi Ayu Pangesti; Abdullah, Nadya Astadewi Putri (Jurusan Akuntansi Politeknik Negeri Malang, 2025)
Abstract: A Greenpreneurship Framework for Okra Business to Global Sustainability Purpose: Developing a sustainable okra business model oriented towards the global market by considering environmental, technological, social, and economic aspects. Method: Utilizing Participatory Action Research by involving consumers, farmers, PT Mitra Tani Dua Tujuh, and community leaders to explore in-depth information on the challenges and opportunities of okra agribusiness. Result: Producing a sustainable business model based on green entrepreneurship that covers the entire okra agricultural value chain from upstream to downstream. Novelty: Integrating sustainability principles comprehensively into okra business management to enhance efficiency and competitiveness. Contribution: Enhancing the competitiveness and sustainability of okra agribusiness through an innovative approach based on environmental sustainability and global market expansion. Abstrak: Kerangka Greenpreneurship Bisnis Okra untuk Keberlanjutan Global Tujuan: Mengembangkan model bisnis okra berkelanjutan yang berorientasi pada pasar global dengan mempertimbangkan aspek lingkungan, teknologi, sosial, dan ekonomi. Metode: Menggunakan Participatory Action Research dengan melibatkan konsumen, petani, PT Mitra Tani Dua Tujuh, serta tokoh masyarakat untuk menggali informasi mendalam terkait tantangan dan peluang agribisnis okra. Hasil: Menghasilkan model bisnis berkelanjutan berbasis kewirausahaan hijau yang mencakup seluruh rantai nilai pertanian okra, dari hulu ke hilir. Kebaruan: Mengintegrasikan prinsip keberlanjutan secara menyeluruh dalam pengelolaan bisnis okra untuk meningkatkan efisiensi dan daya saing. Kontribusi: Meningkatkan daya saing dan keberlanjutan agribisnis okra dengan pendekatan inovatif berbasis lingkungan dan pasar global.